Daya Tahan Atlet Muda di Balik Prestasi: Profil VO₂Max Pemain Sepak Bola Klub Perslotim U-17 - Muhammad Teguh Prasetyo; Catur Prima Eka Putra Abdullah; Rudolof Yanto Basna; Gempa Satria Yudha (MAN Insan Cendekia Jambi, 2026)
This study aims to determine and describe the aerobic capacity profile (VO₂Max) of Perslotim U-17 soccer players as an indicator of the cardiorespiratory endurance of young athletes. The study used a quantitative descriptive method with a test and measurement design. The study population consisted of 50 male athletes aged 16–17 years, selected using a total sampling technique. The instrument used was the Beep Test (multistage fitness test) to measure VO₂Max. Data were analyzed by calculating the mean, minimum, maximum, and standard deviation values, then classified into cardiorespiratory endurance categories based on aerobic fitness norms for adolescent athletes. The results showed that the majority of athletes were in the average (46%) and good (32%) categories, with a small portion in the sufficient (16%), poor (4%), and very good (2%) categories. There were no athletes in the very poor or extraordinary categories. These findings indicate that the players' aerobic capacity is sufficient to support training and match activities, but still has room for improvement. In conclusion, the cardiorespiratory endurance of Perslotim U-17 players is at a fair to good level, so it is recommended to implement a more structured and sustainable aerobic training program to improve the athletes' performance and achievements in the future.